Methodological design of a strategy for the productive and sustainable development of communities in Cauca - Mera Paz, Julián Andrés; Colmenares Quintero, Ramón Fernando (Ingeniería Solidaria, 2023)
Introduction: The productive and sustainable development in the department of Cauca depends to a large extent on the effective use of information and communication technologies (ICT). However, the institutional framework lacks mechanisms or methods to select investment projects with ICT resources. This situation has become an obstacle to economic growth and the improvement of social conditions in the region. Methods: In this article, the construction of a methodological design, one that allows for the selection and evaluation of projects with ICT resources that contribute to the solidarity economy of Cauca communities, is consolidated. The investigative process used a mixed approach, carrying out a systematic review of academic and political-organizational information, after which proposals and selection criteria used in Cauca in the last 5 years were analyzed. Results: With the information collected and analyzed, a route for the selection and evaluation of projects was compiled. Likewise, user stories were used to create a simulator that materializes the process of selecting and evaluating projects in a more efficient and effective way. Conclusions: In conclusion, the creation of the methodological design, materialized in the simulator, represents a valuable tool for the department of Cauca, since it allows for a rigorous and coherent evaluation of investment projects with ICT resources. Originality: Promoting productive growth, the solidarity economy also contributes to sustainable development for the communities of Cauca. Limitations: The sample was limited due to the geographical location of the municipalities.